Regulatory Compliant Tissue-Engineered Human Corneal Endothelial Grafts Restore Corneal Function of Rabbits with Bullous Keratopathy. Issue 1 (December 2017) - Peh, Gary; Ang, Heng-Pei; Lwin, Chan; Adnan, Khadijah; George, Benjamin; Seah, Xin-Yi; Lin, Shu-Jun; Bhogal, Maninder; Liu, Yu-Chi; Tan, Donald; Mehta, Jodhbir
Abstract Corneal transplantation is the only treatment available to restore vision for individuals with blindness due to corneal endothelial dysfunction. However, severe shortage of available donor corneas remains a global challenge. Functional regulatory compliant tissue-engineered corneal endothelial graft substitute can alleviate this reliance on cadaveric corneal graft material. Here, isolated primary human corneal endothelial cells (CEnCs) propagated using a dual media approach refined towards regulatory compliance showed expression of markers indicative of the human corneal endothelium, and can be tissue-engineered onto thin corneal stromal carriers. Both cellular function and clinical adaptability was demonstrated in a pre-clinical rabbit model of bullous keratopathy using a tissue-engineered endothelial keratoplasty (TE-EK) approach, adapted from routine endothelial keratoplasty procedure for corneal transplantation in human patients. Cornea thickness of rabbits receiving TE-EK graft gradually reduced over the first two weeks, and completely recovered to a thickness of approximately 400 µm by the third week of transplantation, whereas corneas of control rabbits remained significantly thicker over 1, 000 µm (p < 0.05) throughout the course of the study. This study showed convincing evidence of the adaptability of the propagated CEnCs and their functionality via a TE-EK approach, which holds great promises in translating the use of cultured CEnCs into the clinic.